Community-Based Sexual and Reproductive Health Promotion and Services for First Nations People in Urban Australia - Hickey S; Roe Y; Harvey C; Kruske S; Clifford-Motopi A; Fisher I; Bernardino B; Kildea S (Dove Medical Press, 2021)
Sophie Hickey,1,* Yvette Roe,1,* Caroline Harvey,2 Sue Kruske,1,2 Anton Clifford-Motopi,2 Ike Fisher,2 Brenna Bernardino,3,4 Sue Kildea1 1Molly Wardaguga Research Centre, Charles Darwin University, Brisbane, Queensland, Australia; 2Institute for Urban Indigenous Health, Brisbane, Queensland, Australia; 3School of Population Health, University of Queensland, Brisbane, Queensland, Australia; 4Poche Centre for Indigenous Health, University of Queensland, Brisbane, Queensland, Australia*These authors contributed equally to this workCorrespondence: Yvette RoeMolly Wardaguga Research Centre, Charles Darwin University, 410 Ann St, Level 11 East Tower, Brisbane, 4000, Queensland, AustraliaTel +61 7 3169 4266Email Yvette.roe@cdu.edu.auContext: Little is known about sexual and reproductive health (SRH) access and health promotion for First Nations peoples in Australia. This study aimed to better understand community preferences, knowledge and access to contraception and SRH services, and use this understanding to make recommendations which support approaches led by local Aboriginal community-controlled health organisations (ACCHOs).Methods: Qualitative First Nations-led yarning circles were conducted with 55 community members and health service providers using and/or working at ACCHOs in urban South East Queensland. Cultural protocols ensured women’s and men’s interviews were separately collected and analysed. Thematic analysis was conducted by multiple coders, privileging interpretations by First Nations researchers.Results: Family, kin and friends were described as key knowledge holders and ACCHOs as knowledge spaces for sharing information about maintaining positive SRH and wellbeing for First Nations people. Interviewees wanted accurate and timely information in an accessible, culturally appropriate way. Making informed choices about family planning was described as an important process of agency and self-determination for First Nations people, and contextualized within broader aspirations for growing strong families and healthy relationships.Conclusion: Understanding SRH through the concept of “knowledge spaces” and “knowledge holders” highlights the collective importance of community relationality to support individual agency and informed SRH decision-making. ACCHOs appear to be acceptable knowledge spaces for SRH information; and evidence-based recommendations may increase their reach. Health services should consider upskilling community SRH knowledge holders to share consistent, accurate and accessible SRH information.Keywords: Indigenous, community-based health promotion, sexual and reproductive health, contraception, strength-based